Effect of Ag nanoparticles on R6G laser dye hosted by PMMA polymerized by plasma jet - Humud, Hammad R. (Iraqi Journal of Physics, 2019)
This work aim to prepare Ag/R6G/PMMA nanocomposite thinfilms by In-situ plasma polymerization and study the changes in theoptical properties of fluorophore due to the presence of Agnanoparticles structures in the vicinity of the R6G laser dye. Theconcentrations of R6G dye/MMA used are: 10-4M solutions wereprepared by dissolving the required quantity of the R6G dye inMMAMonomer. Then Silver nanoparticles with 50 average particlessize were mixed with MMAmonomer with concentration of 0.3, 0.5,0.7wt% to get R6G silver/MMA in liquid phase. The films weredeposited on glass substrates by dielectric barrier discharge plasmajet. The Ag/R6G/PMMA nanocomposite thin films werecharacterization by UV-Visible absorption spectra by using a doublebeam UV-Vis-NIR Spectrophotometer and fluorescenceSpectrophotometer. The thin films surface morphological analysis iscarried out by employing an AFM and SEM. the structure analysisare achieved by X-ray diffraction. The thickness of the films wasmeasured by optical interferometric method. AFM analysis showsthat the surface roughness of plasma polymerized pure PMMA thinfilms was 2.7 nm and for (10-4 R6G + 0.7wt% Ag)Ag/R6G/PMMAthin films was 4.16 nm. The SEM images were indicates that Agnanoparticles (NPs) disperse in the PMMA matrix with uniformdistribution and formed mostly spherical NPs and slightlyagglomerate. Also the silver nanoparticles with 0.7wt%concentration enhances the absorption process by 2.3 times and thefluorescence by 1.7 times. it can be conclude, that the addition of lowconcentrations of silver nanoparticles to the PMMA/ R6G matrix waschanging the optical properties of the prepared nanocomposite thinfilms.